Synthesis of Coumarin-4-ylethyl Phosphonic Acid Derivatives - Kondratyuk, Kostyantyn; Dluzhevskyi, Viacheslav; Mrug, Galyna; Bondarenko, Svetlana; Brovarets, Volodymyr; Frasinyuk, Mihaylo (My University, 2019)
We investigated the reaction of 7-methoxy-4-chloromethylcoumarin and ethyl (diethoxyphosphoryl) acetate in various solvents in the presence of various bases, which led us to the synthesis of ethyl 2-(diethoxyphosphoryl)-3-(7-methoxy-2-oxo-2H-chromen-4-yl) propanoate. It was found that the ratio of 4-chloromethylcoumarin / ethyl (diethoxyphosphoryl) acetate / sodium hydride 1: 2: 2 using dimethylformamide as the solvent was optimal. Alkaline hydrolysis of ester with lithium hydroxide excess affords new 2-(ethoxyphosphoryl)-3-(7-methoxy-2-oxo-2H-chromen-4-yl) propionic acid

Ми досліджували реакцію 7-метокси-4-хлорметилкумарину та етил (діетоксифосфорил) ацетату в різних розчинниках у присутності різних основ, що привело нас до синтезу етил 2-(діетоксифосфорил)-3-(7-метокси-2-оксо-2Н-хромен-4-іл) пропаноату. Встановлено, що оптимальним є співвідношення 4-хлорметилкумарин/етил(діетоксифосфорил) ацетат/гідрид натрію 1 : 2 : 2 з використанням диметилформаміду як розчинника. Лужний гідроліз естеру з надлишком літій гідроксиду дає нову 2-(етоксифосфорил)-3-(7-метокси-2-оксо-2Н-хромен-4-іл) пропіонову кислоту
Keywords: coumarin; phosphonic acid; кумарин; фосфонова кислота; кафедра харчової хімії